2021
DOI: 10.1038/s41598-021-91606-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into TNFR1/MADD death domains in Alzheimer’s disease through conformational molecular dynamic analysis

Abstract: Proteins are tiny players involved in the activation and deactivation of multiple signaling cascades through interactions in cells. The TNFR1 and MADD interact with each other and mediate downstream protein signaling pathways which cause neuronal cell death and Alzheimer’s disease. In the current study, a molecular docking approach was employed to explore the interactive behavior of TNFR1 and MADD proteins and their role in the activation of downstream signaling pathways. The computational sequential and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Molecular docking is a computational approach used to predict the binding conformational behavior of biomolecules, i.e., drugs and proteins. All of the screened drugs were docked and analyzed based on binding affinity (kcal/mol) (see the Supplementary Data S2). From docking results, it has been observed that from 100 FDA-approved drugs, 24 drugs showed binding affinity values higher than −7 kcal/mol and may have good binding potential inside the binding pocket of the EWS protein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Molecular docking is a computational approach used to predict the binding conformational behavior of biomolecules, i.e., drugs and proteins. All of the screened drugs were docked and analyzed based on binding affinity (kcal/mol) (see the Supplementary Data S2). From docking results, it has been observed that from 100 FDA-approved drugs, 24 drugs showed binding affinity values higher than −7 kcal/mol and may have good binding potential inside the binding pocket of the EWS protein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Annotation of the 231 shared SNPs showed that MADD and EFCAB5 harbored the highest number of these variants (nine SNPs). MADD gene, also known as IG20 , plays a critical role in the development of glucose intolerance ( Dupuis et al, 2010 ; Hu et al, 2010 ; Strawbridge et al, 2011 ; Wagner et al, 2011 ) and AD ( Del Villar and Miller, 2004 ; Hassan et al, 2021 ). In accordance with our findings, a large-scale genome-wide cross-trait study identified MADD as the only gene significantly associated with AD and fasting glucose exclusively in pituitary tissue; it is also the only shared gene found in both cross-trait Meta-analysis and Transcriptomic-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is a computational approach usually employed to check the binding potential of biomolecules (Hassan et al, 2022(Hassan et al, , 2021. The modelled 3D structures of hsa-miRNA-3155a and mRNA were docked to analyze the binding potential and nucleotide region involved in the binding conformations.…”
Section: Discussionmentioning
confidence: 99%